2007
DOI: 10.1158/1055-9965.epi-06-0962
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age and Fetal Growth in Relation to Maternal Ovarian Cancer Risk in a Swedish Cohort

Abstract: Background: Pregnancy influences subsequent maternal ovarian cancer risk. To date, there is limited evidence whether two characteristics of pregnancy, gestational age and birth weight, could modify risk. Materials and Methods: We studied 1.1 million Swedish women who delivered singleton births between 1973 and 2001. Information on infant gestational age and birth weight was abstracted from the nationwide Swedish Birth Register. Women were followed prospectively through linkage with other population-based regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 39 publications
1
25
2
Order By: Relevance
“…• A Swedish population-based cohort in 2008 also found a relationship between a high placental weight to an increased risk of developing invasive EOC at a young age [24]. This is consistent with a prior study from the same institution that reported that a low birth weight baby adjusted for gestational age is associated with a reduced risk of developing EOC at an early age (the mean age at diagnosis was 43 years) [25]. • For miscarriage or abortion, most studies found a slightly reduced risk [13,14,17] or no association with EOC [10,15,16].…”
Section: Reproductive Factorssupporting
confidence: 85%
“…• A Swedish population-based cohort in 2008 also found a relationship between a high placental weight to an increased risk of developing invasive EOC at a young age [24]. This is consistent with a prior study from the same institution that reported that a low birth weight baby adjusted for gestational age is associated with a reduced risk of developing EOC at an early age (the mean age at diagnosis was 43 years) [25]. • For miscarriage or abortion, most studies found a slightly reduced risk [13,14,17] or no association with EOC [10,15,16].…”
Section: Reproductive Factorssupporting
confidence: 85%
“…Limitations of the study include: [1] The registries do not contain information on maternal comorbidities (infertility, obesity, diabetes mellitus, preeclampsia), and hence, it is difficult to evaluate bias since some pregnancy complications (e.g., preeclampsia) are considered protective for cancer but significant risk for death of cardiovascular causes [2]; parity was not evaluated as a cofactor due to lack of validated data: Our census database started in the early 1990s and some women included in the study might have given birth before this date [3]; we have no information on family history of cancer [4]; at the end of the follow-up period, only 1 % of women in study population and also in the group diagnosed with cancer were [55 years old, and thus at least for the hormonal-dependent cancers, conclusions should be restricted to women with pre-menopausal cancer [5]; we have no information on specific causes of death [6]; and the follow-up period was rather short; this may bias the results, since VLBW deliveries may be more common in the later years due to advances in fertility treatment and higher percentage of older primipara women, but the short follow-up precludes detecting primary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several strengths of this study: [1] availability of a population-based nation-wide health registry based on unique identity numbers affording valid and efficient study design with adequate follow-up [2]; the birth registry, cancer registry, and death reports completely include the entire population of Israel [3]; all cancer diagnoses are based on histology reports [4]; cancer sitespecific risk estimation [5]; all women may receive antenatal care, preventive medicine services, and ultimately hospitalization and cancer therapy gratis as mandated by the National Health Care Program, thereby minimizing influence of socioeconomic status on outcomes [6]; the criterion of a singleton VLBW is unequivocal and the limit of \1,500 g (\3rd percentile for term newborns) minimizes misclassification; and [7] all types of cancer were studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to breast cancer, several epidemiological studies also reported links between pregnancy characteristics and other types of cancer. These include: a) low age of first gestation increases the risk of cervical cancer (OR=13.1, 95%CI: 3.7-47.3) (Zhang et al, 2013); b) multiple births lower the risk of nonmucinous ovarian cancer (OR=0.71, 95%CI: 0.52-0.98) (Whiteman et al, 2000); c) preterm deliveries endanger women in (RR=2.3, 95%CI: 1.3-3.8) and low birth weight (RR=0.7; 95%CI:0.4-1.0) protects women from developing epithelial ovarian cancer (Mucci et al, 2007) etc. The links between DM and cancer seem to be relatively clear.…”
Section: Discussionmentioning
confidence: 99%